Islamic Boarding School Management to Develop Students' Talents and Interests - Irma Suryani Siregar; Ali Yusron (Al-Hayat: Journal of Islamic Education, 2024)
This study focuses on examining the implementation of Islamic boarding school management in its efforts to develop the talents and interests of students, both in terms of methods and programs carried out by the Islamic boarding school. The approach to this research is qualitative with a case study type. Data and data sources were obtained from the research subjects, namely the Al-Mukhlisin Islamic Boarding School, Padang Lawas, North Sumatra. Data collection techniques were carried out by in-depth interviews with the leaders of the Islamic boarding school, teachers, and students. Direct observation of daily activities at the Islamic boarding school. And documentation of documents and physical evidence at the location. The method used by the Islamic boarding school as the result of the analysis to determine the talents and interests of students is through daily observation, extracurricular activities, interviews, and discussions, as seen from the involvement of students in external competitions. This method allows the Islamic boarding school to see and improve students' talents according to their skills. The programs show comprehensive and structured management implementation, such as extracurricular activities of Tahfidz Al-Qur'an, calligraphy art, music art and various sports. In addition, this Islamic boarding school also routinely sends its students to participate in multiple national and international competitions, which have resulted in various achievements. These programs not only increase the skills and knowledge of students but also form strong characters and personalities by Islamic values. The Islamic boarding school also provides adequate facilities such as laboratories, art rooms, and fields that support activities as extracurricular activities. This study states that effective and innovative management is the primary key to developing the talents and interests of students. The originality of this Islamic boarding school management development research manages various innovative programs that include academic, religious, art, and sports activities and produces various achievements of students in multiple fields.